Preparación de 4-difenilaminosulfonato de sodio - Buehler, M.F.; Mitta, AldoE.A.; Castrillón, José P.A.; López, Rodolfo (Comisión Nacional de Energía Atómica (CNEA), 1961)
Fil:Buehler, M.F. Comisión Nacional de Energía Atómica (CNEA). República Argentina